Interview with Lucille Spooner Dutton, March 5, 1999 - Dutton, Lucille Spooner (Valdosta State University Archives and Special Collections, 1999)
Interview with Lucille Spooner Dutton, Seminole County, Donalsonville (Ga.), March 5, 1999. Blanch Williams present. Fieldworker: Gretchen Geisinger. From the South Georgia Folklife Collection at Valdosta State University Archives and Special Collections.
3 electronic record(s) and derivatives. 766,481,381 bytes. 01:03:30.
Keywords: Oral histories; Georgia; Donalsonville (Ga.); Seminole County (Ga.)